1996
DOI: 10.1029/95gb03295
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the O2/N2 ratio of southern hemisphere air, 1991–1994: Implications for the carbon cycle

Abstract: We present a record of variations in the O2/N2 ratio of air at 41°S latitude from 1991–1994 based on the mass spectrometric analysis of flask samples from Cape Grim, Tasmania, and Baring Head, New Zealand. Results for Cape Grim for the period from June 1991 to February 1992 are in good agreement with previously published data of Keeling and Shertz [1992]. Plotted versus time, O2/N2 ratios show the expected annual cycles. O2/N2 increases in austral spring and summer (caused mainly by net oceanic production) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
111
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 26 publications
8
111
0
Order By: Relevance
“…Measurements of variations in atmospheric oxygen have provided a wealth of insights into the global carbon cycle [Keeling and Shertz, 1992;Keeling et al, 1993Keeling et al, , 1996Bender et al, 1996;Battle et al, 2000]. This is because atmospheric oxygen is in many respects a mirror of atmospheric CO2, caused by the tight link between 02 and CO2 that occurs during the photosynthesis by land plants and the subsequent respiration and remineralization of terrestrial organic matter [Severinghaus, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of variations in atmospheric oxygen have provided a wealth of insights into the global carbon cycle [Keeling and Shertz, 1992;Keeling et al, 1993Keeling et al, , 1996Bender et al, 1996;Battle et al, 2000]. This is because atmospheric oxygen is in many respects a mirror of atmospheric CO2, caused by the tight link between 02 and CO2 that occurs during the photosynthesis by land plants and the subsequent respiration and remineralization of terrestrial organic matter [Severinghaus, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-induced solubility changes also enhance these seasonal O 2 fluxes. Thus, the observed seasonal cycle of APO can be used to evaluate the ocean productivity (Keeling and Shertz, 1992;Bender et al, 1996) and to validate the oceanic O 2 fluxes estimated by different approaches (Keeling et al, 1998b;Balkanski et al, 1999;Garcia and Keeling, 2001). In these studies, oceanic O 2 , CO 2 and N 2 fluxes were used to drive atmospheric transport models to simulate atmospheric APO changes.…”
Section: Introductionmentioning
confidence: 99%
“…Observations have been carried out at ground-based stations (e.g., Bender et al, 1996;Tohjima et al, 2003;Manning and Keeling, 2006;Stephens et al, 2007), sea-based station (van der LaanLuijkx et al, 2010), on oceanographic research/commercial vessels (Tohjima et al, 2005;Battle et al, 2006;Thompson et al, 2007), and from aircraft (Langenfelds et al, 1999;Sturm et al, 2005a). Langenfelds et al (1999), from their measurements over Cape Grim, Australia, reported that the O 2 /N 2 ratio between 0 and 1 km altitude decreased secularly, showing a prominent seasonal cycle, in agreement with surface measurements at the same site.…”
Section: Introductionmentioning
confidence: 99%